Is the underwater gliding test a valid procedure to estimate the swimmers’ drag? - Morais, J.E. (2013)
The aim of this study was to develop a structural equation model for underwater gliding distance based on its determinant variables, in order to confirm whether it is an informative test of young swimmers’ hydrodynamic profile. Methods: Twenty-three subjects (twelve boys and eleven girls with a mean age of 13.61 ± 0.83 years old) were evaluated. The following were determined: (i) the underwater gliding distance; (ii) the squat jump performance; (iii) the passive drag; (iv) the passive drag coefficient; (v) the trunk transverse surface area and; (vi) the gliding velocity. Results: The underwater gliding distance was significantly correlated with the squat jump (rs = 0.47; p = 0.038) and with the coefficient of passive drag (rs = -0.55; p < 0.01) but not with passive drag (rs = 0.41; p = 0.09). The overall model explained 45% of the underwater gliding distance (x2/df = 3.138). Conclusion: The underwater gliding distance seems to be more dependent from the squat jump than from the passive drag. Therefore it seems as if the underwater gliding test is not representative of the swimmers’ passive drag or his /her passive drag coefficient.